A data set of long‐term observation of aquatic vertebrates and associate environmental factors in a temperate stream, the Yura River, Kyoto, Japan. Issue 1 (30th January 2019) - Nakagawa, Hikaru
Abstract: The population dynamics of fishes are strongly affected by habitat characteristics that are constantly changing due to seasonal and interannual variations in climatic, hydrological and geographical processes. Seasonal and interannual variations in hydrological events directly affect the movement, growth and mortality of stream fishes, and indirectly affect their population density and standing crop through changes in local‐scale habitat structures. Characteristics of local‐scale habitats directly affect availability of foods, shelters, spawning sites and interspecific interactions of stream fishes. Therefore, long‐term data regarding the local‐scale dynamics of habitat characteristics and their use by fish species over a few generations or longer would be needed for understanding the mechanism of the determinant process of fish population dynamics. When investigating the effects of habitat changes due to natural processes on the long‐term dynamics of fish populations, removal of artificial influences such as changes in land use, dam constructions and channelization of riverines is often problematic. Thereby, sampling sites where long‐term observation of nonartificial changes in stream fish populations and habitats are very valuable. Here, I report the long‐term seasonal and annual changes in stream fish populations and their habitat characteristics based on 75 snorkeling observations of fishes and environmental measurements in the upper reaches of the Yura River at Ashiu research forest, which has a 36.5 km 2 catchment area with very little artificial disturbance, from May 2007 to June 2018. Snorkeling observations were conducted using the line‐transect method during the day and at night, and microhabitat characteristics (water depth, current velocity, substratum characteristics and the presence/absence of cover) were determined for all individuals observed. A total of 56, 042 individuals were observed, belonging to 17 fish and 7 other aquatic vertebrate species. These data may be used to examine the effects of habitat change on the processes that determine fish populations. Abstract : The long‐term seasonal and annual changes in stream vertebrate populations and their habitat characteristics based on 75 snorkeling observations from May 2007 to June 2018 were reported. Snorkeling observations were conducted using the line‐transect method during the day and at night, and microhabitat characteristics (water depth, current velocity, substratum characteristics, and presence/absence of cover) were determined for all individuals observed. A total of 56, 042 individuals were observed, belonging to 17 fish, six amphibian, and one reptile species.